2005
DOI: 10.1097/01.iop.0000159173.42243.ad
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Disease of the Ocular Adnexa: A Clinical and Pathologic Study With Statistical Analysis of 69 Patients

Abstract: The typical presentation of adnexal lymphoproliferative disease is with a painless mass, swelling, or proptosis; however, pain and inflammation occurred in 20% and 30% of patients, respectively. Stage at presentation, tumor histology, primary or secondary status, and whether the process was unilateral or bilateral were significant variables for disease outcome. In this study, distant spread of lymphoma was lower in patients who received greater than 20 Gy of orbital radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 66 publications
3
62
0
Order By: Relevance
“…[9][10][11] Clinical manifestations of the orbital lymphomas include swelling and prolapses of the eyelid, painless but palpable masses, and exophthalmia and oculomotor defects. 12 These clinical findings are neither specific nor early signs of the development of primary orbital lymphomas. Early diagnosis can only be made with a needle biopsy.…”
Section: -8mentioning
confidence: 98%
“…[9][10][11] Clinical manifestations of the orbital lymphomas include swelling and prolapses of the eyelid, painless but palpable masses, and exophthalmia and oculomotor defects. 12 These clinical findings are neither specific nor early signs of the development of primary orbital lymphomas. Early diagnosis can only be made with a needle biopsy.…”
Section: -8mentioning
confidence: 98%
“…As a result of the known incidence of late local and systemic recurrence and mortality, we believe that these patients should be followed for life, in conjunction with the treating oncologist and the family practitioner. 11,39 When CT-PET becomes more widely available, this may become the preferred technique, considering this combines functional and anatomical information simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Anatomical site was divided into orbital, conjunctival, lacrimal sac, and eyelid lesions, based on clinical, imaging, and intra-operative findings, as previously defined. 11 The CT scanning of the ocular adnexae was performed using axial and direct coronal 2-mm contiguous slice imaging, with administration of intravenous contrast. The images were evaluated by a single observer (TJS) for location, circumscription, density, enhancement with contrast media, moulding to adjacent structures, calcification, tissue invasion, and bone destruction.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphoma is the most common orbital malignancy, has a predilection for the elderly, and classically presents as painless proptosis or adenexal swelling over a duration of 5-7 months. 7,9 Non-Hodgkin's lymphoma is reported 11 to have an orbital presentation in 2.4% of all non-Hodgkin's lymphoma cases, while its prevalence is about 5% in systemic NHL. 9 According to Liang et al, 12 the incidence of secondary central nervous system lymphoma in a patient with orbital non-Hodgkin's lymphoma is 5.9%, and the most common form of central nervous system involvement in lymphoma is leptomeningeal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common type is either follicular, 12% to 23%, or DLBCL, 7% to 21%, depending on the study. [4][5][6][7][8][9] The frequency of ocular adnexal lymphoma with localization to the orbit has been cited as 54%. 5 It has been suggested that it may be more appropriate to analyze ocular 10 found that for secondary ocular adnexal lymphoma, follicular type is most common (33%-66%) followed by (in approximate decreasing frequency) multiple myeloma/plasmacytoma, lymphoplasmocytic lymphoma/immunocytoma, mantle cell lymphoma, DLBCL, Burkitt lymphoma, MALT lymphoma and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%